Potential of interleukin-7 in sepsis as a biomarker and therapeutic agent: a narrative review - Zhang, Tong; Liu, Han; Tie, Yi-fu; Meng, Tian-wei; Liang, Qun (Frontiers in Medicine, 2025)
ObjectiveThis study seeks to examine the dynamics of endogenous interleukin-7 (IL-7) and its associated regulatory factors in sepsis, and to elucidate the mechanisms by which exogenous IL-7 may confer therapeutic benefits. The ultimate objective is to evaluate its dual potential as a clinical biomarker and as a novel therapeutic agent.MethodWe searched PubMed, Embase, and Web of Science from inception to April 24, 2025, using terms such as Interleukin-7, CD127, CYT107, interleukin-7 receptor, sepsis, septic shock, and lymphopenia.ResultsIn sepsis, endogenous IL-7 levels rise from a low baseline and may remain elevated for a prolonged period. Exogenous IL-7 can enhance immune function, regulate inflammation, and exert anti-apoptotic effects. Endogenous IL-7 levels may represent a potential prognostic indicator in sepsis. Exogenous IL-7 may modulate immune function in patients with clinical sepsis but does not reduce mortality.ConclusionEndogenous IL-7 is closely associated with sepsis, whereas exogenous IL-7 shows promise for aiding the recovery of patients with sepsis, although further research is required.